2009
DOI: 10.1002/pro.281
|View full text |Cite
|
Sign up to set email alerts
|

The Hofmeister effect on amyloid formation using yeast prion protein

Abstract: A variety of proteins are capable of converting from their soluble forms into highly ordered fibrous cross-b aggregates (amyloids). This conversion is associated with certain pathological conditions in mammals, such as Alzheimer disease, and provides a basis for the infectious or hereditary protein isoforms (prions), causing neurodegenerative disorders in mammals and controlling heritable phenotypes in yeast. The N-proximal region of the yeast prion protein Sup35 (Sup35NM) is frequently used as a model system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 38 publications
8
63
0
Order By: Relevance
“…Our data confirm an inverse Hofmeister effect on Sup35NM aggregation, which agrees with our previous work (18) and with observations for other amyloidogenic proteins that allow this conclusion while not explicitly stating it (41,42,44). An inverse Hofmeister trend arises when a colloidal particle is positively charged and hydrophilic or when a particle is negatively charged and hydrophobic (55).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data confirm an inverse Hofmeister effect on Sup35NM aggregation, which agrees with our previous work (18) and with observations for other amyloidogenic proteins that allow this conclusion while not explicitly stating it (41,42,44). An inverse Hofmeister trend arises when a colloidal particle is positively charged and hydrophilic or when a particle is negatively charged and hydrophobic (55).…”
Section: Discussionsupporting
confidence: 93%
“…These results confirm the ostensibly "inverse" Hofmeister trend previously observed (18). Having established that ion-specific effects greatly affect aggregation rate, we examined the structural and biological effects of these differing rates.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…For example, Yeh et al have reported evidence for Hofmeister effects of inorganic ions on amyloid formation of a yeast prion protein, 103 but there are counterexamples, where no correlations with Hofmeister rankings were found. 104 In fact, there are no convincing arguments in favour of a general Hofmeister-type behaviour of protein aggregation because conformational changes and aggregation reflect different molecular interactions.…”
Section: Conformational Versus Colloidal Stabilitymentioning
confidence: 99%
“…26 and 27), thus supporting the observation of increased thermal and chemical stability of HypT upon the addition of NaCl or L-arginine. However, salt ions can also promote aggregation (29) and fibrillation of proteins such as HypF, insulin, and prion proteins (28,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%